A Conceptual Overview of Sustainable Entrepreneurship - Saoudi, Nedjoua; MEDJAHDI , Fateh; BRAHIMI , Charaf (Finance and Business Economies Review, 2017)
Nowadays, sustainability and sustainable development is slowly gathering momentum in public speech, but greater attention and reverence in academic research. In today’s rapidly changing world of innovation and technology, entrepreneurship is considered as the main driver of economic growth. However, the notion of sustainable entrepreneurship is rather recent and its definition is still emerging. Accordingly, this paper attempts to identify particularly the concept of sustainable entrepreneurship, by illustrate its dimensions and relations with other relevant concepts, and introducing an integrated conceptual model to fully embrace the meanings and practices of sustainable entrepreneurship, to ends the paper with a brief conclusion.